Hypocholesterolemic Effect of Chitin and its Hydrolysed Products in Albino Rats - P.T., Mathew; K.G., Ramachandran Nair (Fishery Technology, 2025)
Male albino rats (Wistar strain) were fed with diets supplemented with chitin, partially hydrolysed chitin and glucosamine hydrochloride (0.5% of the diet) for 13 weeks. During the course of the experimental feeding no significant difference in growth rate was observed for the above three groups compared to the animals of control group. There was significant decrease in lipid deposition, and cholesterol levels in muscle, serum, liver, kidney and heart of the experimental animals. It was more pronounced in the chitin- and PH chitin fed groups of animals. Difference in digestibility of chitin and derivatives were also not significant.